(untitled) (Journal of Computational Mathematics, 2006)
In this paper, the superconvergence results are derived for a class of boundary control problems governed by Stokes equations. We derive superconvergence results for both the control and the state approximation. Based on superconvergence results, we obtain asymptotically exact a posteriori error estimates.